Poor Parenting, Attachment Style, and Dating Violence Perpetration Among College Students - Tussey, Brian Ermon (Journal of interpersonal violence, 2021)
Although dating violence is prevalent among college students, little is known about how both attachment style and participation in risky behaviors contribute to this pattern of violence. To address this literature gap, we examine the role of poor parenting, child abuse, attachment style, and risky sexual and drug use behaviors on dating violence perpetration among 1,432 college students (51% female). Path analysis results revealed that females were more likely to report greater attachment anxiety but lower attachment avoidance compared with males. Correlates of attachment anxiety included child physical abuse, witnessing parental violence, and poorer maternal relationship quality whereas attachment avoidant behavior was linked to more physical abuse and poorer maternal relationship quality. Females were more likely to perpetrate dating violence as were those with greater attachment anxiety and lower attachment avoidance. Other correlates of dating violence perpetration included sexual and drug risk behaviors. Finally, distal factors (i.e., more child physical abuse and poorer maternal relationship quality) also were associated with dating violence perpetration. Study implications are also discussed.